1994
DOI: 10.1099/0022-1317-75-1-207
|View full text |Cite
|
Sign up to set email alerts
|

Expression, characterization and purification of simian immunodeficiency virus soluble, oligomerized gp160 from mammalian cells

Abstract: The envelope glycoprotein, gp160, of human (HIV) and simian (SIV) immunodeficiency viruses mediates virushost cell binding followed by fusion of the viral and plasma membranes. The envelope proteins are known to exist as non-covalently associated oligomers on the virus surface. The production of permanent mammalian cell lines that constitutively secrete relatively high levels of soluble forms of SIV gpl60 is described and we show that these proteins are secreted predominantly as tetramers with lower levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Evidence from expression studies of soluble envelope glycoprotein containing gp120 fused to the gp41 ectodomain (2,18,19,43) as well as of membrane-bound full-length gp160 (17,44,45) support the view that the envelope glycoprotein is a trimer or a tetramer. Although the trimeric nature of vesicular stomatitis virus (46) and rabies virus (47) envelope glycoproteins has been determined using virion-derived envelope, relatively little is known about the oligomeric nature of the HIV envelope on virions (5,6).…”
Section: Resultsmentioning
confidence: 97%
“…Evidence from expression studies of soluble envelope glycoprotein containing gp120 fused to the gp41 ectodomain (2,18,19,43) as well as of membrane-bound full-length gp160 (17,44,45) support the view that the envelope glycoprotein is a trimer or a tetramer. Although the trimeric nature of vesicular stomatitis virus (46) and rabies virus (47) envelope glycoproteins has been determined using virion-derived envelope, relatively little is known about the oligomeric nature of the HIV envelope on virions (5,6).…”
Section: Resultsmentioning
confidence: 97%
“…Two vectors pTH.tat and pTH.rev contain the respective re6 genes into the BamHI site without upstream Ub-R. The SIV macJ5 molecular clone was used as the source of these genes as previously described [2,10,12]. Vector pND14-G1 expressed the SIV mac239 envelope gp120 coding sequence under control of the hCMV IE enhancer/promotor.…”
Section: Dna Expression Vector Based Vaccinesmentioning
confidence: 99%
“…Recombinant MVA [15] in this study were engineered to express the gag/pol, nef, tat, re6, and en6 genes of SIV macJ5 [10,12] under transcriptional control of vaccinia virus-specific promoters. Briefly, the gag/pol, nef, tat and re6 coding sequences from the SIV mac32HJ5 molecular clone [10,12] were placed under control of vaccinia virus early/late promoter P7.5 by insertion into the unique SmaI site of the MVA vector plasmid pUCII-LZ-P7.5 [16]. The SIV mac32HJ5 en6 coding cDNA was cloned into the MVA vector plasmids pIII-sP and pIIIgpt-sP to allow for recombinant gene expression regulated by a strong synthetic vaccinia virus promoter (Table 1) [17].…”
Section: Mva Based Vaccinesmentioning
confidence: 99%
“…SIV-infected cells have been reported to produce dimers of full-length precursor and TM subunit env (8). Similarly, a soluble uncleaved recombinant SIV env lacking the transmembrane domain and cytoplasmic tail (gp140) was reported to form tetramers and dimers (9). Chemical crosslinking and sucrose gradient sedimentation suggested that full-length or soluble uncleaved HIV-1 precursor occurred as dimers and higher-order oligomers (10).…”
mentioning
confidence: 99%